Plan de gestion de incidentes que afectan a los equipos informáticos de la ESPAM MFL - Cuzme Romero, María Gabriela (2015)
This research aims to develop a management plan for incidents affecting the computers of the Polytechnic School of Manabi Agricultural Manuel Felix Lopez, establishing courses of action to reduce the impact of incidents and improve user productivity. To this end, the Incident Management ITIL methodology, which is divided into four phases paragraph was employed: Registration, included the determination of the computers, which were identified and ranked the risks to which they were exposed by the MAGERIT (version 3.0) methodology, concluding with the registration of computer incidents; allowed qualifying set priority levels for each incident according to criteria of urgency and impact; through the stages of diagnosis and resolution service agreements between the personnel and equipment of the IT department managers and career-MFL ESPAM they were developed. Based on the results obtained through the Incident Management Plan, the impact of such events was limited, with the assignment of a team responsible for managing them, a situation that checks with service agreements made, so when performing the procedures incident response you can contain and mitigate them, it is therefore appropriate to adopt effective measures to protect information assets from security institution.